Free Fasciocutaneous versus Muscle Flaps in Lower Extremity Reconstruction: Implications for Functionality and Quality of Life - List, Emile B.; Hahn, Brett A.; Qiu, Shan S.; de Jong, Tim; Rakhorst, Hinne A.; Verheul, Elfi M.; Maarse, Wiesje; Coert, J. Henk; Krijgh, David D. (Journal of Reconstructive Microsurgery, 2024)
Free tissue transplantations are commonly used to treat complex lower extremity defects caused by trauma, vascular disease, or malignancy, particularly when vital structures are exposed. This study aimed to expand the knowledge on patient-reported outcomes by comparing fasciocutaneous and muscle flaps, with the goal of facilitating patient counseling. Additionally, patient-level risk factors associated with decreased functioning and health-related quality of life were identified.This retrospective, cross-sectional, multicenter study included patients who underwent microsurgical lower extremity reconstruction using free fasciocutaneous or muscle flaps between 2003 and 2021, with a minimum follow-up of 12 months. Data were collected from medical records, pain scores, Short-Form 36 (SF-36), and Lower Extremity Functional Scale (LEFS). Mean scores were compared between flap types and predictors of LEFS, SF-36 mental component summary (MCS), and SF-36 physical component summary (PCS) scores were determined using a backward stepwise regression model.Of the 206 patients eligible, 100 (49%) were included in the retrospective part. A total of 89 (43%) responded to the questionnaires, with 62 treated using a fasciocutaneous flap and 27 with a muscle flap. No significant differences in total LEFS, SF-36 PCS, or MCS scores were found between the two flap type. Pain was a significant predictor of decreased functional outcomes for both flap types and was also linked to poorer mental health in patients treated with fasciocutaneous flaps. Other predictors of low patient-reported outcome scores included obesity, diabetes, poorer mental health, and a follow-up of less than 2 years.Patients treated with fasciocutaneous and muscle flaps experience comparable levels of functionality and quality of life after surgery. Flap selection should be based on defect characteristics, along with the surgeon's individual skills and preferences. A comprehensive approach that considers physical comorbidities, pain, and mental health is essential, as these factors significantly impact patient functionality and quality of life.
Keywords: lower leg; free flap; reconstruction